(untitled) (BSAA arte, 2019)
Thanks to the works of recovering of the wall paintings of the Chamber of Doña Sancha in the Royal Collegiate Church of St Isidore of León, today we can see, on the one hand, a magnificent ensemble of Renaissance grisailles that narrate a cycle of the life of Christ and remained hidden almost from the very same moment of their creation and, on the other hand, a set of oil wall paintings made in the same art style that contain three important iconographic cycles: the Crucifixion, the Conversion of St Augustine and the life and miracles of St Isidore of Seville. This offers us a new reading of the space consistent with the life of the canons the 16th century.